Social brain, social dysfunction and social withdrawal - Porcelli, Stefano; Van Der Wee, Nic; van der Werff, Steven; Aghajani, Moji; Glennon, Jeffrey C.; van Heukelum, Sabrina; Mogavero, Floriana; Lobo, Antonio; Olivera, Francisco Javier; Lobo, Elena; Posadas, Mar; Dukart, Juergen; et al. (Neuroscience and biobehavioral reviews, 2019)
•The human brain shows several levels of specialization for social stimuli processing.•Social brain could be affected by several neuropsychiatric disorders.•Mechanisms underlying social dysfunction are largely similar across disorders.•Social dysfunction and social withdrawal may represent a transdiagnostic domain.•A better understanding of their biological underpinnings may lead to new treatments. The human social brain is complex. Current knowledge fails to define the neurobiological processes underlying social behaviour involving the (patho-) physiological mechanisms that link system-level phenomena to the multiple hierarchies of brain function. Unfortunately, such a high complexity may also be associated with a high susceptibility to several pathogenic interventions. Consistently, social deficits sometimes represent the first signs of a number of neuropsychiatric disorders including schizophrenia (SCZ), Alzheimer’s disease (AD) and major depressive disorder (MDD) which leads to a progressive social dysfunction. In the present review we summarize present knowledge linking neurobiological substrates sustaining social functioning, social dysfunction and social withdrawal in major psychiatric disorders. Interestingly, AD, SCZ, and MDD affect the social brain in similar ways. Thus, social dysfunction and its most evident clinical expression (i.e., social withdrawal) may represent an innovative transdiagnostic domain, with the potential of being an independent entity in terms of biological roots, with the perspective of targeted interventions.